PROBLEMATIKA SEKOLAH INKLUSI DI PERBATASAN - Nuraini Nuraini (CV. ADIBA AISHA AMIRA, 2022)
Schools providing inclusive education need to be supported by Special Educator Teachers in the learning process and in developing children with special needs in general. Problems that arise between one another when studied in depth can be interconnected, such as problems with students, teachers, schools, government, or the community. With regard to the problem of teachers, teachers have complaints where there is a lack of competence related to handling ABK (Children with Special Needs) where the cause is the lack of understanding of teachers related to inclusive schools and ABK which further impacts on the problem of difficulties. Problems in these inclusive schools include: learning problems in class, problems with facilities and infrastructure, problems with educators, problems with collaboration between parents, the community and the business world. It needs optimal management of all elements that hold the process of success of inclusive schools, especially at the border.